2010
DOI: 10.4314/acsj.v16i1.54349
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical transmission and survival of bacterial wilt on enset

Abstract: The transmission of enset bacterial wilt with contaminated knives and the survival of the causal agent in soil and enset plant debris was studied at the Awassa Agricultural Research Center, Awassa, Ethiopia. Contaminated knives were found to transmit the pathogen from infected to healthy plants. Disease symptoms were recorded within 15 and 21 days after inoculation on plants inoculated at 6 and 12 months after transplanting, respectively. Enset plants inoculated at 24 and 36 months after transplanting showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Infected soil, vehicles and tools move the blood disease pathogen within plantations and planting material and fruits are capable of spread at long distances (Buddenhagen, 2009). In contrast, the survival period of Xcm bacteria is limited, ranging from 9 to 35 days in plant debris or soil (Mwebaze et al, 2006; Welde-Michael et al, 2008) and saprophytic survival outside the host is limited, due to relatively slow multiplication rates, compared with Ralstonia or Pseudomonas (Biruma et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Infected soil, vehicles and tools move the blood disease pathogen within plantations and planting material and fruits are capable of spread at long distances (Buddenhagen, 2009). In contrast, the survival period of Xcm bacteria is limited, ranging from 9 to 35 days in plant debris or soil (Mwebaze et al, 2006; Welde-Michael et al, 2008) and saprophytic survival outside the host is limited, due to relatively slow multiplication rates, compared with Ralstonia or Pseudomonas (Biruma et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Bacterial ooze exudes, when nondry part of the plant is removed. The disease mainly spreads through infected farm tools, infected planting materials (since the plant requires repeated transplanting that damage the corm and roots), animals that fed on infected plants and possibly insects feeding on the foliage (Welde-michael et al, 2008b). Survival of the pathogen is mainly through infected plant debris and infected soil (Mwebaze et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It can cause yield losses of up to 100% (Yemataw et al, 2016) and all cultivated varieties are susceptible (Merga et al, 2019), although some variation in level of susceptibility/tolerance has been reported (Welde-Michael et al, 2008a;Wolde et al, 2016). Control methods available to farmers are limited to basic phytosanitary practices involving the removal of the diseased plants, disinfection of farm tools, and use of clean planting materials (Tadesse et al, 2003;Welde-Michael et al, 2008b). So far they have had little effect in curbing the disease.…”
Section: Introductionmentioning
confidence: 99%